Confinamiento y calidad de vida de los estudiantes del III ciclo de Ingeniería de Sistemas - Universidad Nacional de Trujillo, 2021 - Alfaro Velarde, Pamela Alexandra (2022)
This thesis was made with the purpose of analyzing the influence of the confinement in the quality of life of the students of the III cycle of the Professional School of Engineering of Systems, National University of Trujillo, it is intended to know how it has influenced the fact to live in confinement in the different dimensions that make up the quality of life, such as physical well-being, emotional well-being, interpersonal relationships and personal development. A sample was taken from 40 students of the III cycle of the P.S. of Systems Engineering, to work with them, methods such as inductive, deductive and statistical were put into practice, in addition to the fact that techniques such as the survey and the interview were applied to obtain quantitative and qualitative data respectively. This research is relevant to Social Work, because it is a topic that is being explored recently and generates an impact for our professional intervention, since these are people with whom we work normally, university students, but, in a different context, at a distance, since social confinement. The thesis is divided into seven chapters, which are: I. Introduction, here it delves into the problematic reality, background to this research, the theoretical bases on which I have based myself to carry out the research and the conceptual framework of the most relevant terms; II. Materials and methods, for the compilation of statistical data and the application of techniques and instruments; III. Presentation of results, the results obtained in each of the dimensions mentioned are shown; IV. Discussion of results, deepens the results by comparing them with theoretical information and relying on qualitative information of the target population; V. Conclusions; VI. Recommendations; VII. Bibliographic references and VIII. Annexes.